ANALYSIS OF THE INTERPRETATION OF THE CONCEPT OF “REFLECTION”, “REFLECTIVE SKILLS” IN SCIENTIFIC LITERATURE (Pedagogy of Higher and Secondary Education, 2007)
The paper is devoted to the analysis of different approaches to the notion “reflexion” and “reflexire sldlls” in literature on Pedagogics and Psychology.